Increased risk of ventricular tachycardia in patients with sarcoidosis during the very long term follow-up. (1st February 2017) - Te, Abigail Louise D.; Lin, Yenn-Jiang; Chen, Yun-Yu; Chung, Fa-Po; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Tuan, Ta-Chuan; Chao, Tze-Fan; Liao, Jo-Nan; Lin, Chin-Yu; Chang, Yao-Ting; et al.
Abstract: Background: Sarcoidosis is an important diagnostic consideration in patients with ventricular tachycardia (VT) of unknown origin. The clinical course of VT as the primary presentation in patients with sarcoidosis is mostly unknown. This study aimed to investigate the incidence of life-threatening VT and mortality during long term follow-up in patients with sarcoidosis. Methods: We analyzed the epidemiological features of sarcoidosis in Taiwan using the National Health Insurance Research Database from 2000 to 2004. Patients with sarcoidosis were identified, and healthy controls without prior histories of structural heart disease were matched with a 1:1 propensity-score to the sarcoidosis group. The risk of life-threatening VT and mortality with sarcoidosis was analyzed. Results: A total of 2237 sarcoidosis cases were enrolled with a matching number of healthy controls, and the baseline characteristics between the two groups were similar. After a mean follow-up of 11.4 ± 2.15 years (IQR: 12, 11.3–12), the VT incidence in the sarcoidosis group was higher than in healthy controls (0.94% [85 per 100, 000 person-year] in the sarcoidosis group, and 0.09% [8 per 100, 000 person-year] in healthy controls). After a multivariate adjustment including the sex, age, and other comorbidities, the VT risk was still higher in the sarcoidosis group (hazard ratio: 12.7, 95% confidence interval: 2.82–56.9; P < 0.001). The risk of defibrillator implantations for secondary prevention, cardiovascular death, and total mortality between the groups was equivalent. Conclusions: Sarcoidosis may increase the predisposition to ventricular arrhythmias with a cumulative incidence of 0.94% during a very long term follow-up of nearly 10 years from initially diagnosing sarcoidosis.